Hubungan Capital Intensity Ratio, Firm Size, Digital Transformation terhadap Tax Avoidance dengan CSR sebagai Moderasi - Karlinah, Lady; Tallane, Yoan Yohana; Putri, Vallerie Redyna (Owner : Riset dan Jurnal Akuntansi, 2024)
This research analyzes how Firm Size, Digital Transformation, and Capital Intensity Ratio influence Tax Avoidance, with Corporate Social Responsibility as a moderator. "This research targets non-cyclical and cyclical consumer companies listed on the Indonesia Stock Exchange between 2020 and 2022. This research uses purposive sampling and produces 62 companies and 186 data points from 2020 to 2022. This research uses Eviews 12.0 to panel data regression analysis. The panel data test, Chow test, and Hausman test were then run simultaneously to quantify the data." The research results show that Firm Size, Capital Intensity Ratio, and Digital Transformation all help avoid taxes. CSR regulations will reduce the Tax Avoidance effect of Capital Intensity Ratio, Firm Size, and Digital Transformation.